2009
DOI: 10.1111/j.1751-1097.2008.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Halorhodopsin from Natronomonas pharaonis Forms a Trimer Even in the Presence of a Detergent, Dodecyl‐β‐d‐maltoside

Abstract: Halorhodopsin (HR) is a transmembrane seven-helix retinal protein, and acts as an inward light-driven Cl ) pump. HR from Natronomonas pharaonis (NpHR) can be expressed in Escherichia coli inner membrane in large quantities. Here, we showed that NpHR forms the trimer structure even in the presence of, whose concentrations are much higher than the critical micelle concentration (0.17 mM M). This conclusion was drawn from the following observations. (1) NpHR in the DDM solution showed an exciton-coupling circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 36 publications
9
49
0
Order By: Relevance
“…This NpHR in DDM-solubilized state was prepared from the recombinant E. coli cells and thus did not form complexes with Brub. The solubilized NpHR is known to be in a trimeric state like in the KM-1 membrane, albeit without Brub [37]. In Panel D, the spectra at varying Cl − concentration are shown without scattering subtraction and their difference spectra are shown in Panel E. As shown in Panel E, a Cl − induced blueshift in the NpHR spectrum results in smooth bilobes in the 450-720 nm region with an isosbestic point at 597 nm.…”
Section: − Induced Brub Spectral Change In the Dark Statementioning
confidence: 92%
“…This NpHR in DDM-solubilized state was prepared from the recombinant E. coli cells and thus did not form complexes with Brub. The solubilized NpHR is known to be in a trimeric state like in the KM-1 membrane, albeit without Brub [37]. In Panel D, the spectra at varying Cl − concentration are shown without scattering subtraction and their difference spectra are shown in Panel E. As shown in Panel E, a Cl − induced blueshift in the NpHR spectrum results in smooth bilobes in the 450-720 nm region with an isosbestic point at 597 nm.…”
Section: − Induced Brub Spectral Change In the Dark Statementioning
confidence: 92%
“…46 Similar to other archaeal rhodopsins, phR possesses a proline residue (Pro132) that is responsible for a kink in the middle of helix C. Previous structural analyses of BR's reaction intermediates have shown that the extracellular part of helix C undergoes a large movement upon formation of the M state. 37,[47][48][49] Because key residues (Arg123, Tyr124 and Trp127) in this moiety are conserved in phR, it seems possible that during the ion pumping cycle of phR the extracellular part of helix C undergoes the same conformational change as that observed during the proton pumping cycle of BR. It is noteworthy that the morphology of the central open space in the trimeric assembly is conserved between phR and BR (or aR2).…”
Section: Structural Comparison Between Phr and Brmentioning
confidence: 96%
“…These observations suggest that the trimeric phRbacterioruberin complex found in the C2 crystal is close to the quaternary structure that phR forms under the physiological conditions. 37 The central part of the trimer is filled with lipid molecules. The electron density map suggested that the extracellular half of this region contains three phospholipids.…”
mentioning
confidence: 99%
“…However, because the cells do not synthesize retinal, an alternative role for the actinorhodopsin apoprotein cannot be ruled out. Many microbial rhodopsins oligomerize in the membrane and form large aggregates (55)(56)(57)(58)(59)(60). Without a cofactor, actinorhodopsin might still aggregate in the membrane, providing structural stability against membrane stresses.…”
Section: Discussionmentioning
confidence: 99%